2020
DOI: 10.17979/sportis.2020.6.3.6527
|View full text |Cite
|
Sign up to set email alerts
|

El desarrollo del respeto en la formación deportiva: una revisión sistemática

Abstract: La práctica deportiva bien orientada puede fomentar al desarrollo valores tales como el respeto, el autocontrol, el esfuerzo, la autonomía y el liderazgo. En este sentido, el objetivo de este estudio fue doble: 1) realizar una revisión sistemática relativa a las investigaciones que examinaban los efectos de alguna intervención sobre el desarrollo del respeto en la formación de jóvenes deportistas; y 2) describir y analizar dichas intervenciones. Para tales fines, se llevó a cabo una revisión sistemática en la … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…In another systematic review [45] where this model and the Sports Education model were analyzed, positive effects were also found on the level of respect for social conventions, respect for rules and referees, total commitment and respect for opponents, and improving fair play. The success of this model is also verified in the extracurricular environment and sports activities [46]. Finally, it is worth noting the conclusion pointed out by Pozo et al [47] after carrying out a systematic review of 22 studies, which indicated that research with a longer intervention period is necessary; thus, carrying out a longer follow-up, quantitative methodological designs, and studies with a larger sample size is crucial.…”
Section: Teaching Personal and Social Responsibility Model (Tpsr)mentioning
confidence: 66%
“…In another systematic review [45] where this model and the Sports Education model were analyzed, positive effects were also found on the level of respect for social conventions, respect for rules and referees, total commitment and respect for opponents, and improving fair play. The success of this model is also verified in the extracurricular environment and sports activities [46]. Finally, it is worth noting the conclusion pointed out by Pozo et al [47] after carrying out a systematic review of 22 studies, which indicated that research with a longer intervention period is necessary; thus, carrying out a longer follow-up, quantitative methodological designs, and studies with a larger sample size is crucial.…”
Section: Teaching Personal and Social Responsibility Model (Tpsr)mentioning
confidence: 66%